PERANCANGAN APLIKASI PENGENALAN ALAT-ALAT LITURGI MENGGUNAKAN AUGMENTED REALITY BERBASIS MOBILE - Pertiwi, Rahayu Putri; Nurhayati, Oki Dwi; Isnanto, Rizal (STMIK Budi Darma, 2019)
Catholicism, is one of the recognized religions in Indonesia. Today many Catholics do not know about their own means of worship. Therefore it is necessary to conduct a study to create an Android application with Augmented Reality technology as an alternative introduction to liturgical devices. The development of this application uses the Multimedia Development Life Cycle. This application will display 3D object visualization of liturgical instruments along with a Description Panel and buttons for sounding, and allows users to zoom in, zoom out and move objects. The application is built using Blender3D, Unity3D, and Vuforia SDK. Results of application testing are the function keys on the application 100% successful. The ideal detection results are obtained in a room with a light intensity of at least 38 lux and a maximum of 180 lux, a distance of 15-30 cm, and an angle of 60o-90o. Testing the detection of barrier markers, the ideal result of 100% success is shown if the marker is not blocked by anything.